Prevalence and severity of diabetic retinopathy in patients attending the endocrinology diabetes clinic at Mulago Hospital in Uganda. (June 2019) - Magan, Tejal; Pouncey, Anna; Gadhvi, Kunal; Katta, Mohamed; Posner, Marcus; Davey, Clare
Abstract: Aims: The epidemiology for diabetic retinopathy (DR) has been well described in the western population. Countries in Sub-Saharan Africa have attempted to identify the prevalence of diabetic eye disease, however, there still remains a degree of paucity across the continent due to inadequacy in health system organisations and resource poor settings. We aimed to identify the severity and prevalence of DR and maculopathy of patients attending the diabetes clinic at Mulago Hospital, Kampala, Uganda. Methods: A cross-sectional observational study of 44 patients who attended a diabetes clinic at Mulago Hospital in April 2016. Parameters measured included visual acuity (VA) using a Snellen chart, blood glucose (mmol/l) and blood pressure (mmHg). Screening for DR grading was carried out with indirect fundoscopy and retinal photograph. Only the highest graded eye of retinopathy of each patient was included. Results: A total of 41 eyes from 41 patients were included. Of these patients 15 were male. The average age of patients was 50.4 years. Six eyes (14.6%) had a VA < 6/18. Prevalence of DR was 19.5% (8 eyes) and 14.6% (6 eyes) had maculopathy. Of all eyes 14.6% had sight-threatening retinopathy, which was 85.7% of total cases of retinopathy in our study. Conclusions: We observed a high prevalence of DR and maculopathy, particularly sight threatening retinopathy, considering the proportion of patients screened. There is a need for a co-ordinated diabetes screening service through integration of the diabetes clinic and eye clinic at Mulago Hospital to better identify and treat this sight-threatening condition.